2011
DOI: 10.1158/1078-0432.ccr-11-0184
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Peptide Vaccination Combined with Temozolomide: A Clinical Trial in Stage IV Melanoma Patients

Abstract: Purpose: The study is a proof-of-principle trial evaluating toxicity, immune response, and clinical response in melanoma patients after combined therapy with temozolomide and the telomerase peptide vaccine GV1001. Our previous GV1001 trials showed immune responses in approximately 60% of lung or pancreatic cancer patients. Experimental Design: Twenty-five subjects with advanced stage IV melanoma (M1B or M1C) received concomitant temozolomide and GV1001. Temozolomide was administered 200 mg/m2 or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 52 publications
7
80
1
Order By: Relevance
“…Another promiscuous TERT-derived CD4 epitope called GV1001 was reported by Gaudernack and colleagues (48). This peptide has been used in clinical trials with encouraging results when combining to CT in melanoma and NSCLC (25,26). Nevertheless, the impact of spontaneous GV1001-specific immune response on vaccination efficiency and clinical outcome has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promiscuous TERT-derived CD4 epitope called GV1001 was reported by Gaudernack and colleagues (48). This peptide has been used in clinical trials with encouraging results when combining to CT in melanoma and NSCLC (25,26). Nevertheless, the impact of spontaneous GV1001-specific immune response on vaccination efficiency and clinical outcome has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore TERT activity has been observed in all studied cancer forms, including stem cell-like tumor cells (23) and is therefore a hallmark of cancer cells (24). Furthermore, recent clinical studies using a TERT-derived CD4 epitope vaccine called GV1001 was able to increase survival of cancer patients when combined with radio or CT (25,26). These results suggested the interplay between anti-TERT-CD4 T-cell immunity and conventional anticancer therapy.…”
Section: Introductionmentioning
confidence: 91%
“…In our GV1001 vaccine trials, we have observed immune response rates ranging from 50% to 80%, combined with low toxicity. [1][2][3][4] None of the patients experienced serious adverse events. Interestingly, the GV1001 immune response was associated with improved survival in all trials.…”
Section: Most Cancer Vaccines Have Focused On Recruiting Cd8mentioning
confidence: 95%
“…This includes studies in melanoma, non-small cell lung cancer (NSCLC), and pancreatic cancer patients evaluating vaccination with the telomerase peptide GV1001. [1][2][3][4] Human telomerase reverse transcriptase (hTERT) is overexpressed in most human cancers and thus a widely applicable target for cancer therapy. 5,6 Because hTERT expression is important for tumor growth, the risk of tumor escape is presumably limited.…”
Section: Most Cancer Vaccines Have Focused On Recruiting Cd8mentioning
confidence: 99%
See 1 more Smart Citation